Temperature-controlled ablation of the mitral isthmus line using the novel DiamondTemp ablation system - Rottner, Laura; My, Ilaria; Schleberger, Ruben; Moser, Fabian; Moser, Julia; Kirchhof, Paulus; Ouyang, Feifan; Rillig, Andreas; Metzner, Andreas; Reissmann, Bruno (Frontiers in Cardiovascular Medicine, 2022)
Background: Recently, the novel DiamondTempTM (DT)-catheter (Medtronic®) was introduced and allows for high-power, short-duration ablation in a temperature-controlled mode. Aim: To evaluate the feasibility, efficacy and safety of the DT-catheter for bidirectional block of the mitral isthmus line (MIL) using two different energy dosing strategies. Methods: Twenty patients with recurrence of atrial fibrillation and/or atrial tachycardia following pulmonary vein (PV) isolation were included. All patients underwent reisolation of PVs in case of electrical reconnection and creation of a MIL using the DT-catheter. Ablation settings were a catheter-tip temperature limit of 60°C, a temperature-controlled power of 50W with an application duration of 10 (group A, n=10) or 20 seconds (group B, n=10). Additional epicardial ablation from within the coronary sinus was performed, if bidirectional block could not be achieved with endocardial ablation only. Results: Bidirectional block of the MIL was achieved in 19/20 (95%) patients. Mean procedure and fluoroscopy time, and dose area product for group A and group B were 109±26 vs. 104±35 min (p=0.70), 12±4 vs. 13±5 min (p=0.39), and 451 [348; 658] vs. 487 [344; 572] cGycm (p=0.65). In group B, bidirectional block of the MIL required significantly fewer radiofrequency-applications when compared to group A (26±12 vs. 42±17, p=0.04). Additional epicardial ablation was required in 8/10 patients (80%) of group A and in 5/10 (50%) patients of group B (p=0.34). No major complication occurred. Conclusion: Ablation of the MIL using the DT-catheter is highly effective and safe. Longer radiofrequency-applications appear to be favorable without compromising safety.